Influence of Geographical Conditions on the Spatial Structure of Jayapura City - Baharuddin, Alfini; Wibisono, B Hari; Prayitno, Budi; Roychansyah, M Sani (Universitas Muhammadiyah Surakarta, 2016)
Jayapura City is situated in the eastern tip of Indonesia and borders the neighboring country Papua New Guinea (PNG).Â Its geographical conditions are very diverse dominated by hills leading to the formation of separated urban areas. Currently, there are two major urban areas, Jayapura and Abepura. Historically, Jayapura and Abepura were two old towns established in the Dutch rule, namely Hollandia Haven and Hollandia Binnen. They are detached by Skyline hills that hinder their complete physical merger.Â The presence of two separated urban areas in Jayapura City is also reinforced by the image perceived by the residents regarding with the powerful visual image of those cities. It however forms unique and distinctive properties in the spatial structure of Jayapura City.Â This study examines how the influence of geographical conditions on the spatial structre of Jayapura City. Data collection was done through direct observation and interviews with respondents of Jayapura and Abepura. Direct observation was conducted to obtain data on the use of land that form patterns in Jayapura City area. While collecting data through questionnaires conducted to determine the image of residents of Jayapura City on the spatial structure of the city. The results showed that the geographical conditions in Jayapura City affect the formation of two separate parts of the city. Â The geographical condition is also an element forming a strong spatial structure as a characteristic reinforces the visual impression of the existence of two cities in a âsingle cityâ.